INVESTIGATION OF THE DIAGNOSTIC ACCURACY OF MALARIA RAPID DIAGNOSTIC TEST IN PATIENTS WITH RECURRING MALARIA SYMPTOMS - Audu, Funmilola; Usman, Mohammed Aliyu; Usman, Hauwa Salisu; Nuhu, Abubakar (FUDMA JOURNAL OF SCIENCES, 2024)
Accurate diagnosis and proper treatment are central to breaking malaria transmission cycle and eradication of malaria especially in an endemic country as Nigeria Malaria rapid diagnostic test RDT is a simple and effective diagnostic tool There is rise in the use of RDT in malaria diagnosis in Nigeria however its accuracy in patients with recurring malaria symptoms is unclear This study evaluated the efficacy of Plasmodium falciparum histidinerich protein 2 based rapid diagnostic test RDT in the diagnosis of malaria in patients with recurring malaria symptoms Microscopy was used as the reference method for diagnosis Giemsa and Field stained thick and thin smear were used to count and detect malaria parasite The results showed that out of 100 participants examined a total prevalence of 85 percent Giemsa stain 83 percent Fields stain was recorded for microscopy while and 36 percent was recorded for RDT Additionally we observed that there was no significant difference p005 in the parasite density observed in both Giemsa and Fields staining technique Conclusively our study revealed that RDT is not effective in diagnostic tool in patients with recurring malaria symptoms therefore microscopy is still the gold standard for malaria diagnosis